The Effect of Job Involence and Organizational Justice on Organizational Citizenship Behavior with Organizational Commitment as a Mediating Variable - Yuliana, Ita; Zuhriyah, Eni; Pramesti, Diesyana Ajeng (Borobudur Management Review, 2025)
This study aims to examine and analyze the effects of job involvement and organizational justice on organizational citizenship behavior (OCB), with organizational commitment serving as a mediating variable among employees of PUDAM Tirta Agung, Temanggung Regency. The research employed a quantitative approach, using questionnaires as the primary data collection instrument. A purposive sampling technique was applied, involving 100 employees with a minimum tenure of one year. Data were analyzed using multiple regression analysis with SPSS 25.0. The findings reveal that job involvement has no significant effect on OCB, while organizational justice shows a positive and significant influence on OCB. Furthermore, job involvement has no significant impact on organizational commitment, and organizational justice demonstrates a negative but insignificant effect on organizational commitment. Additionally, organizational commitment does not significantly influence OCB. The mediation tests indicate that organizational commitment does not mediate the effects of either job involvement or organizational justice on OCB. These results suggest that employees’ perceptions of fairness within the organization play a more critical role in encouraging extra-role behaviors than job involvement or commitment levels.